Proceedings of the Beyond Vision and LANguage: InTEgrating Real-World kNowledge (LANTERN) 2019
DOI: 10.18653/v1/d19-6408
|View full text |Cite
|
Sign up to set email alerts
|

At a Glance: The Impact of Gaze Aggregation Views on Syntactic Tagging

Abstract: Readers' eye movements used as part of the training signal have been shown to improve performance in a wide range of Natural Language Processing (NLP) tasks. Previous work uses gaze data either at the type level or at the token level and mostly from a single eyetracking corpus. In this paper, we analyze type vs token-level integration options with eye tracking data from two corpora to inform two syntactic sequence labeling problems: binary phrase chunking and part-of-speech tagging. We show that using globally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The inductive bias of language processing models can be improved using the eye-tracking signal (Barrett et al, 2018;Klerke and Plank, 2019) and the modification leads to more "human-like" output in generative tasks (Takmaz et al, 2020;Sood et al, 2020b). This indicates that patterns of relative importance in computational representations 1 Our implementation adapts code from https:// pypi.org/project/textualheatmap/.…”
Section: Patterns Of Relative Importancementioning
confidence: 99%
“…The inductive bias of language processing models can be improved using the eye-tracking signal (Barrett et al, 2018;Klerke and Plank, 2019) and the modification leads to more "human-like" output in generative tasks (Takmaz et al, 2020;Sood et al, 2020b). This indicates that patterns of relative importance in computational representations 1 Our implementation adapts code from https:// pypi.org/project/textualheatmap/.…”
Section: Patterns Of Relative Importancementioning
confidence: 99%
“…Here, English gaze data were used to improve POS induction for French. Klerke and Plank (2019) also found that predicting a gaze feature as an auxiliary task may help POS tagging a multitask learning setup.…”
Section: Using Gaze For Sequence Labelling and Sequence Classificationmentioning
confidence: 99%
“…Barrett et al (2016a), (2016b) showed that word‐type averages of gaze features helped POS induction better than token‐level features. Klerke and Plank (2019) found that word‐type variance was better than less aggregated gaze features. Using word‐type gaze features does not require gaze at test time.…”
Section: How To Use Gaze For Nlp?mentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous work in gaze-supported NLP has used gaze as an input feature, e.g. for syntactic sequence labeling [36], classifying referential versus non-referential use of pronouns [82], reference resolution [30], key phrase extraction [86], or prediction of multi-word expressions [64]. Recently, Hollenstein et al [29] proposed to build a lexicon of gaze features given word types, overcoming the need for gaze data at test time.…”
Section: Gaze Integration In Neural Network Architecturesmentioning
confidence: 99%